The effect of different root canal sealers on the fracture resistance of endodontically treated teeth-in vitro study - Anuve Hrishi Phukan; Shivani Mathur; Meera Sandhu; Vinod Sachdev (Wolters Kluwer Medknow Publications, 2017)
Background: The aim of this study was to compare the in vitro effects of four different root canal sealers on the fracture resistance of endodontically treated teeth. Materials and Methods: Seventy-five freshly extracted human mandibular premolars were used for the study. Teeth were divided into five groups based on type of root canal sealers used. Gutta-percha was used for all the samples: Group I: AH Plus root canal sealer, Group II: MTA Fillapex root canal sealer, Group III: Apexit root canal sealer, Group IV: Conventional zinc oxide-eugenol (ZOE) sealer, Group V: Control (unobturated teeth). The teeth were embedded in acrylic resin blocks and fracture force was measured using a universal testing machine (Asian Test Equipments). Data obtained were statistically evaluated using one-way ANOVA and post hoc test (Tukey's test). All groups showed statistically significant result (P < 0.05). Results: Group I and Group II showed higher resistance to fracture than other three groups. There was comparable difference in fracture force between Group I and Group II. Moreover, there was no statistically significant difference between Group III and Group IV and between Group IV and Group V. Conclusion: Based on this in vitro study, resin-based sealer was more effective as compared to other sealers and the control group. However, no significant differences were observed between ZOE and control group.